"Fear, greed, and dedication": the representation of self-entrepreneurship in international English textbooks - Yuto Wahyuto; Joko Nurkamto (Journal on English as a Foreign Language, 2022)
A number of studies have reported neoliberal representation in English textbooks in a variety of contexts around the world. However, the study focusing on self-entrepreneurship as one of the critical neoliberal tenets is scantily addressed. To fill this void, the present study seeks to investigate the representation of self-entrepreneurship deliberately inculcated in English textbooks. Anchored in critical discourse analysis and Halliday’s Systemic Functional Linguistics (SFL), this study investigated three Business English textbooks used in higher education in Indonesian. The findings of the study revealed that the English textbooks employed role-playing, presenting celebrity and fame, exhibiting famous entrepreneur figures, presenting the distinct image of entrepreneurial figures, and portraying entrepreneur figures through article or literature to disseminate self-entrepreneurship notions displayed in a variety of discourses. The findings of the current study call to equip educational practitioners (e.g., teachers, policymakers, book designers) with critical thinking skills as well as provide them practical tools to interrogate ideology, norms, and values encapsulated within curriculum artefacts such as language textbooks.